Natural experiments from Earth Hour reveal urban night sky being drastically lit up by few decorative buildings - Chu Wing So; Chun Shing Jason Pun; Shengjie Liu; Sze Leung Cheung; Ho Keung Kenneith Hui; Kelly Blumenthal; Constance Elaine Walker (Scientific Reports)
Abstract Light pollution, a typically underrecognized environmental issue, has gained attention in recent years. While controlling light pollution requires sustained efforts, Earth Hour offers a unique natural experimental setting to assess temporary lights-out measures. Using photometric and spectroscopic sensors, we observed up to 50% night sky darkening during Earth Hour from 2011 to 2024 in Hong Kong, primarily as a result of a small but critical number of lights-out instances in central business districts, as evidenced by crowd-sourced photography records. Weekend lighting pattern in the city during Earth Hour remained unaffected. The emission reductions mostly occurred in the 445–500, 500–540, and 615–650 nm spectral ranges—corresponding to peak emissions from LED billboard screens— and in the 585–595 nm range, associated with metal halide floodlights used for facades and billboards. Our study identifies these sources as major contributors to urban light pollution. By combining multimodal observations, we offer a comprehensive assessment of light pollution sources and the potential benefits of sustainable lighting practices in urban environments. This research highlights the importance of targeted light pollution mitigation efforts and provides critical insights for policymakers to enhance urban sustainability and human well-being.